Edukasi Manajemen Keuangan Sejak Dini : Membangun Generasi Melek Finansial di SMP Negeri 5 Gunungsitoli - Serniati Zebua; Mitra Setia Zebua; Indah Laila Gea; Asria Harefa; Silvia Pis Mendrofa; Lipus Martin Luter Buulolo; Overnius Mendrofa; Hironimus Iman Syukur Waruwu; Elisabet Santa Tibelaris Bate’e; Sepfis Arifman Lase; Desni Krisdayanti Mendrofa; Lides Fransiska Gea (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The financial literacy rate in Indonesia, recorded at 49.68% (OJK, 2022), indicates that most people do not have adequate understanding of personal financial management. This condition poses a struggle to cultivating a financially literate generation starting at a young age. Through this community service activity, a financial management education program was carried out at SMP Negeri 5 Gunungsitoli with a participatory and contextual approach. This program aims to strengthen students' comprehension of fundamental financial concepts, foster self-efficacy, and form healthy financial attitudes and habits. The methods used were interactive lectures, pocket money management simulations, and group discussions, with 30 grade VIII students as participants. The results of the pre-test and post-test indicated a significant improvement in understanding, rising from 30% to 86.7%.. This activity provides practical implications that financial literacy education needs to be systematically integrated into the basic education curriculum, and adapted to the digital challenges faced by today's youth. Therefore, this activity is anticipated to serve as an educational model that can be replicated in other schools to foster a financially literate young generation capable of navigating the challenges of the modern economy.